2021
DOI: 10.1017/dmp.2021.215
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Stress and Stress Busters Used Among Saudi Dental Practitioners During the COVID-19 Pandemic Outbreak

Abstract: Aim: This study aims to assess the stress levels, stress busters (stress relievers), and coping mechanisms among Saudi dental practitioners (SDPs) during the COVID-19 pandemic outbreak. Methodology: Self-administered questionnaire was sent to SDPs via Google forms. Cohen’s stress score scale was used for stress evaluation, and the mean scores were compared based on age, gender, qualification, and occupation. In addition, comparisons of the utilization of stress coping mechanisms and stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
1
8
0
1
Order By: Relevance
“…In our study, the most common coping mechanisms participants stated were calling friends and colleagues over phone/video calls or using social media. The latter was similar to other research where electronic media and entertainment were reported to be common stress busters [34].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the most common coping mechanisms participants stated were calling friends and colleagues over phone/video calls or using social media. The latter was similar to other research where electronic media and entertainment were reported to be common stress busters [34].…”
Section: Discussionsupporting
confidence: 91%
“…Our scoping review was also guided by the PRISMA guidelines for scoping reviews (Tricco et al, 2018). Brief summary of relevant findings Additional comments (Aldhuwayhi et al, 2021) Cross Saudi Arab Unclear 296 adult dentists (30% women). Race/ ethnicity N/R…”
Section: Methodsmentioning
confidence: 99%
“…These measures are very strictly acclaimed to control the spread of COVID-19 disease and to protect the people from this pandemic. Nevertheless, a lack of understanding of the COVID-19 risk factors among people has been observed worldwide [10,17]. People's understanding and adherence to preventive measures play an essential part in controlling the contraction of COVID-19 [9].…”
Section: Introductionmentioning
confidence: 99%